Municipal Wastewater Sludge Evaluation from the Cities of Pernik and Veliko Tarnovo- Agricultural Application Potentials - Kathijotes, Nicholas; Marinova, Svetla (My University, 2009)
In recent years, 68 in number sewage / wastewater treatment stations were constructed and entered into service. There was then a large increase in available biological sludge which was piling up in the area of stations hindering its function and polluting the environment. The aim of this paper is to present an assessment of the sludge produced in biological wastewater treatment in the WWTP of the cities of Pernik and Veliko Tarnovo. Sludge was investigated in terms of agrochemical and chemical parameters, the content of organic pollutants, its sanitary-microbiological technological indicators and helminths, based on Bulgarian legislation related to the use of sludge in agricultural practices. Results showed that biomass residues are rich in macro and trace elements and can be used to maintain and enhance plant yield and for the reclamation of disturbed land and not only. This is valid provided that sludge meets the requirements of the regulations.
Keywords: Sludge; Wastewater treatment